Evaluasi Koleksi Perpustakaan Berdasarkan Pandangan Edward G. Evans dan Elizabeth Futas - Siti Munisah (Pustabiblia: Journal of Library and Information Science, 2020)
Evaluation of the collection as part of the activity of collection development the library has a significant influence for the existence of the collection in the library. Course evaluation activities collection it is the idea or the important thing towards the improvement of the collection, to be able to better understand, observe, correct and weighing the collection for the improvement and advancement of the library collection. Technically written by Evans and Futas, both of which have standards and processes as well as methods in the evaluation of such a collection, which can be used as reference material or input for the evaluation activities of the collection. The formulation of the problem in this thesis is to understand how to view or how to describe the evaluation of the collection of the views of evans and futas with a more concise and clear. The method used in this paper is a literature study with a description of the analysis of the writings of Edvans and Futas directly with the reinforced by the writing of other works. The results of this paper is to describe the theory of the evaluation of the collection according to the authors of Evans and Futas on the procedures and methods of evaluation of library collections, the summary is clearly based on the writings of both the authors who the author is. The conclusion of the second author (Evans and Futas), which are from both the evaluation of the collection the library has the means and methods are almost the same in doing so, the need and importance of evaluation of the collectionis a means of planning against the collection in a library.